Identification of impact of minor actinide addition on burnup process and heavy nuclide evolution in UN-PuN fueled small modular gas-cooled fast reactors - Aula, Mila Hidayatul; Syarifah, Ratna Dewi; Rasidi, Ahmad Haris; Shodiq, Abdulloh Hasan; Shodiq, Muhammad Husein; Palupi, Bekti; Trianti, Nuri; Su’ud, Zaki (Eastern-European Journal of Enterprise Technologies, 2026)
The object of this study is a small modular gas-cooled fast reactor (GFR) fuelled by UN-PuN with minor actinides (MA) addition. The problem solved in this study is the identification of the impact of MA addition on the criticality, fuel burnup stability, and nuclear waste transmutation of the small modular GFR. The parameters studied include k-eff, macroscopic cross-section, conversion ratio (CR), heavy nuclides inventory, and the probability of radiopharmaceutical isotope production. The study was conducted using SRAC-COREBN computational analysis, and the MA used in this study were Pa-231, Am-241, and Np-237. The results obtained that the MA addition, on average, results in a decrease in k-eff, the magnitude of which depends on the type and concentration of MA. Macroscopic cross-section analysis reveals shifts in values, such as an increase in the Macroscopic cross-section absorption, particularly in the case of Am-241. Then, an increase in the macroscopic cross-section of fission is passed at high energies. The CR > 1 and inversion ratio of heavy nuclide approximately are observed at 50% in all configurations. Furthermore, the evolution of fission products such as Tc-99, Rh-105, and I-135 suggests the chance production of radiopharmaceutical isotope. Interpretation of the results show that adding MA effect k-eff and CR because isotopes such as Am-241, Np-237, and Pa-231 actively participate in fission and conversion of fissile material using fast neutron spectrum. A key feature of obtained results is a stable burnup profile, where the MA effectively functions in target transmutation without disrupting the consumption of the primary fissile fuel. These findings could be a technical basis for supporting national energy security and sustainable nuclear waste management.